Three Bianthraquinone Derivatives from the Mangrove Endophytic Fungus Alternaria sp. ZJ9-6B from the South China Sea - Huang, Cai-Huan (Molecular Diversity Preservation International, 2011)
Three new bianthraquinone derivatives, alterporriol K (1), L (2) and M (3), along with six known compounds were obtained from extracts of the endophytic fungus Alternaria sp. ZJ9-6B, isolated from the mangrove Aegiceras corniculatum collected in the South China Sea. Their structures were elucidated by one- and two-dimensional NMR spectroscopy, MS data analysis and circular dichroism measurements. Compounds 1, 2 and 3 were first isolated alterporriols with a C-2–C-2′ linkage. The crystallographic data of tetrahydroaltersolanol B (7) was reported for the first time. In the primary bioassays, alterporriol K and L exhibited moderate cytotoxic activity towards MDA-MB-435 and MCF-7 cells with IC(50) values ranging from 13.1 to 29.1 μM.